Starotestamentalna typologia krzyża Jezusa Chrystusa = The Old Testament typology of the cross of Jesus Christ - Juckiewicz, Piotr (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
In the article, the author discusses the Old Testament figures of the symbol of the cross, thus presenting the range of meanings and the depth of this sign. On the basis of the results of research carried out using the heuristic method, the analysis and the synthetic-critical ones, it presents the process of shaping the understanding of the sign of the cross in mentality of believers in the early ages of Christianity.
Keywords: krzyż; figury; symbol; przygotowanie staurologiczne; cross; figures; staurological preparation